Novel clinicopathological and molecular characterization of metanephric adenoma: a study of 28 cases - Ying Ding; Cong Wang; Xuejie Li; Yangyang Jiang; Ping Mei; Wenbin Huang; Guoxin Song; Jinsong Wang; Guoqiang Ping; Ran Hu; Chen Miao; Xiao He; et al. (BMC, 2018)
Abstract Background Metanephric adenoma is a rare, benign renal neoplasm with occasional misdiagnosis. However, its molecular characterization is not fully understood. Methods In this study, we use the hybrid capture-based Next-Generation Sequencing to sequence a panel of 295 well-established oncogene or tumor suppressor genes in 28 cases of MA patients in China. Novel clinicopathological markers associated with the mitogen-activated protein kinase (MAPK) pathway in metanephric adenoma were detected by immunohistochemistry. Results It was found that except for BRAF (22/28) mutations (c.1799 T > A, p.V600E), NF1 (6/28), NOTCH1 (5/28), SPEN (5/28), AKT2 (4/28), APC (4/28), ATRX (3/28), and ETV4 (3/28) mutations could also be detected. Meanwhile, a novel and rare gene fusion of STARD9-BRAF, CUX1-BRAF, and LOC100507389-BRAF was detected in one MA patient. In addition, although MEK phosphorylation was normally activated, the phosphorylation level of ERK was low in metanephric adenoma cases. Highly expressed p16 and DUSP6 may have contributed to these results, which maintained MA as a benign renal tumor. Conclusions This study provides novel molecular and pathological markers for metanephric adenoma, which could improve its diagnosis and increase the understanding of its pathologic mechanism.